Fungal Endophyte: An Interactive Endosymbiont With the Capability of Modulating Host Physiology in Myriad Ways - Sarkar, Sohini; Dey, Abhijit; Kumar, Vinay; Batiha, Gaber El-Saber; El-Esawi, Mohamed A.; Tomczyk, Michał; Ray, Puja (Frontiers in Plant Science, 2021)
Endophytic fungi ubiquitously dwell inside the tissue-spaces of plants, mostly asymptomatically. They grow either intercellularly or intracellularly in a particular host plant to complete the whole or part of their life cycle. They have been found to be associated with almost all the plants occurring in a natural ecosystem. Due to their important role in the survival of plants (modulate photosynthesis, increase nutrient uptake, alleviate the effect of various stresses) they have been selected to co-evolve with their hosts through the course of evolution. Many years of intense research have discovered their tremendous roles in increasing the fitness of the plants in both normal and stressed conditions. There are numerous literature regarding the involvement of various endophytic fungi in enhancing plant growth, nutrient uptake, stress tolerance, etc. But, there are scant reports documenting the specific mechanisms employed by fungal endophytes to manipulate plant physiology and exert their effects. In this review, we aim to document the probable ways undertaken by endophytic fungi to alter different physiological parameters of their host plants. Our objective is to present an in-depth elucidation about the impact of fungal endophytes on plant physiology to make this evolutionarily conserved symbiotic interaction understandable from a broader perspective.